EFFECT OF NITROGEN FERTILIZER ON GROWTH, YIELD AND YIELD COMPONENTS OF MAIZE (ZEA MAYS L.) IN DECHA DISTRICT, SOUTHWESTERN ETHIOPIA - Woldesenbet, Mitiku; Haileyesus, Asnakech (International Journal of Research -GRANTHAALAYAH, 2016)
Maize response to high nitrogenous fertilization levels is a means among other means to know maximum productivity, from this perspective, a field nitrogen management trial using five N levels (0, 23, 46, 69 and 92 kg N/ha) with three replications. The study was conducted in 2015 in Decha District, ModyoGomberaKebele of Kaffa Zone, SNNPR State. The experiment was laid out in RCBD. The result of this study indicated that effects of different rates of N fertilizer had influenced the growth and yield components of maize. The tallest plant (360.66 cm) was recorded from the application of 92 kg N ha-1 and the shortest (347.33 cm) from no N application. The ANoVA for the number of kernels per ear showed that the lowest kernels per ear (497.86) were obtained from no N application and the highest kernels per ear (588) were obtained from the application of 92 kg N ha-1 although there was no significant difference between the application of 69 and 92 kg N ha-1. Regarding to ear length the data showed that the longest ear (23.63 cm) was obtained from the application of 92 kg N ha-1. The effect of N on grain yield indicated that there is no significant difference between the application of 69 and 92 kg N ha-1 even if there is a slight difference on yield. Generally, maximum N fertilization level (92 Kg N/ha) in this study area showed increase in growth and yield components (number of kernels per ear and ear length). However the application of 69 kg N ha-1 seems adequate to get the optimum yield.